Energy load on first wall components in high density, small ELM regimes in ASDEX Upgrade. (March 2023) - Redl, A.; Eich, T.; Vianello, N.; David, P.; ,; ,
Abstract: A set of dedicated shots with constant heating power combining NBI (Neutral Beam Injection) and ECRH (Electron Cyclotron Resonance Heating) have been executed at the ASDEX Upgrade (AUG) tokamak using a highly shaped small ELM magnetic geometry in order to investigate the differences on heat loads at the first wall of AUG by means of the revised cooling water calorimetry. The flattop fuelling has been varied on a shot-to-shot basis while keeping constant all the other parameters, exploring a large range of the density operational space of AUG. Reducing the fuelling rate allows a gradual transition from small ELM regime at high density into a Type-I ELMy H-mode. Additionally, the safety factor q has been increased/decreased by changing B tor, which leads also to variations in the heating scheme. With the lowest flattop fuelling, reaching a Type-I ELMy H-mode, a fraction of ∼ 6% of calorimetrically captured energy loads at the first wall normalized against the entire calorimetrically captured energy has been recorded, whereas in the highest fuelling case, being in a small ELM scenario, the first wall heat loads are increased up to 16%. Considering all cases reveals an almost linear trend between the fraction of energy deposited at the first wall and the turbulence control parameter α t . This observation is consistent with an enhancement of the filamentary activity at higher α t, when the plasma turbulence is dominated by resistive interchange modes at the separatrix. Highlights: First results for scaling the first wall heat loads in AUG are presented. The reliability of the calorimetric measurements is ensured by providing the global energy balance. The results suggest that the first wall heat loads follow the turbulence control parameter α t almost linearly. The results indicates that the enhanced filamentary transport does not cause a change in the power deposition, but rather a change in the distribution of the power deposition on the PFCs.